The Effect of Using Facebook as a Learning Media Towards Improving Learning Outcomes - Darwin; Warneri; Eny Enawaty; Dewi Fajaryati; Juhata (INTERNATIONAL PENELITI EKONOMI, SOSIAL, DAN TEKNOLOGI, 2024)
The aim of this research is to determine the effect of using Facebook as a learning medium on improving learning outcomes. The design of this research is a Literature Review which was carried out in March 2024 with a sample size of 7 journals. Writing this article uses stages in the methodology such as: selecting a review topic, searching for literature, analyzing the literature and writing a review. The research results show that there is an influence of the use of Facebook media on learning outcomes because by using Facebook learning becomes fun. There is no effect of using Facebook media on learning outcomes because some students only use Facebook to fill their free time, not as a medium for learning.